A CLINICAL STUDY ON THE EFFECTIVENESS OF AVARTHAKI CHOORNA IN PRAMEHA W.S.R. TO DIABETES MELLITUS (International Journal of Ayurveda and Pharma Research, 2020)
With a prevalence rate of 424.9 million globally and 72.9 million in India, the disease Diabetes Mellitus affects a large population in our society. The prospective understanding of this disease from etiology to complication is when understood, retrospective analysis of the same in Ayurvedic perspective is characterized by Prabhoota and Avila Mootrata due to the accumulation of excess Medas in Basti leading to Prameha. The same can be understood by the theory of Osmtic diuresis in Diabetes Mellitus. The drug Virapreeta Lajjalu explained in Rajanighantu is used in the study, which has direct reference for Prameha and has not been evaluated yet. Aim: To assess the effectiveness of Avarthakichoorna in the management of Prameha w.s.r to Diabetes Mellitus and to evaluate the quality of life. Materials and Methods: A single blind clinical study where 21 patients were given the Avarthaki Choorna for a period of 14 days. Observation and Results: The statistical analysis of study revealed that the intervention was beneficial in Prabhoota Mootrata with a p value